PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS - Dea Aprilia; Neneng Hasanah (Publika Citra Media, 2026)
This research aims to empirically prove the effect of Capital Structure, Firm Size and Sales Growth on Financial Distress. This research was conducted at Consumer Cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The type of research is quantitative. The type of data used in this research is secondary data. Samples were collected using the purposive sampling method. The number of samples was 17 companies, observation data for 5 years of the research period, the data collected 85. The data was processed using the Eviews 12 program to test the hypothesis using panel data regression analysis. The results of the F statistical test showed that Capital Structure, Firm Size, and Sales Growth simultaneously affected Financial Distress. While partially (t test) showed that Capital Structure and Firm Size had a negative effect on Financial Distress, while Sales Growth partially had no effect on Financial Distress.